Composite Classic Hodgkin Lymphoma and Follicular Lymphoma: A Clinicopathologic Study of 22 Cases With Review of 27 Additional Cases in the Literature. (24th June 2022) - Huang, Yuhua; Hu, Shimin; Larson, Daniel P.; Shi, Min; He, Rong; Dave, Bhavana J.; Greiner, Timothy C.; Fu, Kai; McPhail, Ellen D.; Ketterling, Rhett P.; Medeiros, L. Jeffrey; Yuan, Ji
Abstract : Composite classic Hodgkin lymphoma and follicular lymphoma (CHLFL) is a rare and poorly characterized entity. Herein, we report the clinicopathologic features of 22 cases of CHLFL from 3 institutions and we assess 27 additional cases reported in the literature. In our cohort (n=22), patients with CHLFL had a median age of 61 years and an equal male to female incidence. Most cases (95%) arose de novo with the remaining patients having a history of non-Hodgkin lymphoma. CHLFL always involved lymph nodes (100%) and most cases (95%) revealed 2 distinct areas separately diagnostic for CHL and FL. The CHL component represented a variable proportion of the overall neoplasm (5% to 90%) and was either mixed cellularity (82%) or nodular sclerosis (18%) type. The Hodgkin/Reed-Sternberg cells expressed CD30 (100%), PAX5 (100%), CD15 (62%), BCL6 (47%), BCL2 (29%), and EBER (25%), in a polymorphous inflammatory background typical of CHL. The FL component was low-grade in 55%, grade 3A in 36%, and grade 3B in 9% of cases. All 3 cases investigated by cytogenetic methods for a clonal relationship between the CHL and FL components were clonally related. These clinicopathologic features of our cohort are similar to those of cases reported in the literature. The 5-year overall survival in combined patients with CHLFL (n=49) was 48%, comparable to CHL but worse than FL in the elderly. In summary, CHLFL is a rare entity that most often occurs in older adults, involves lymph nodes, and most commonly presents de novo. In the small number of cases assessed, the CHL and FL components are usually clonally related suggesting that the CHL and FL components may share a common progenitor B-cell, likely a mutated germinal center B-cell.